Light absorption enhancement using Graphene Quantum Dots and the effect of N-719 dye loading on the photoelectrode of Dye-Sensitized Solar Cell (DSSC) - Mohamed Sharif, Noor Fadzilah; Ab Kadir, Mohd Zainal Abidin; Shafie, Suhaidi; Md Din, Muhamad Faiz; Yusuf, Yusnita; Samaila, Buda (Scientific.Net, 2022)
Graphene quantum dots (GQDs) is used to enhance light absorption in the visible region of DSSC by sensitising method. The used of GQDs in photoelectode may effect the N-719 dye loading on photoelectrode and the study is done by ultraviolet spectroscopy (Uv-Vis). Initially, the TiO2 photoelectrode films is sensitised in ∼5 nm GQDs to overcome TiO2 photoelectrode drawback such as random electron transport and short-circuit current. Then, photoelectrode films is sensitised in N-719 dye to excite the electrons in TiO2 film. PG 7.5 adsorbed only 0.103 x 10-7 mol cm-2 N719 dye while PT at 0.527 x 10-7 mol cm-2. The pristine TiO2 photoelectrode (PT) adsorbed more than 80.4% of N-719 dye compared to PG 7.5 photoelectrode and other TiO2-GQDs photoeletrodes (PG 2.5, PG 5.0 and PG 10). As a result, the used of GQDs for TiO2 photoelectrode is reduced the intake of expensive N-719 dye for DSSCs. This happened because some of the functional groups in the GQDs solution such as hydroxyl and carboxyl groups are biocompatible with TiO2 which allows more adsorption sites of GQDs onto TiO2 surface. Thus, after GQDs molecules were occupied on the TiO2 surface, not many sites were available for N719 dye molecule. Therefore, it might reduce the N719-dye intake in the DSSC device, which can reduce the fabrication cost of DSSC and give good impact on environment.